2021
DOI: 10.1155/2021/9927196
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Origanum majorana L. Methanolic Extract on Bile Duct Ligation in Male Rats

Abstract: Introduction. Cholestasis is caused by malfunction of the hepatobiliary system. This disorder is the result of the accumulation of bile fatty acids and other toxins in the liver. The aim of the current study was to investigate the antioxidative and hepatoprotective effects of methanolic extract of Origanum majorana L. (OM) on hepatic disorder and tissue damage induced by bile duct ligation (BDL) in rats. Materials and methods. Twenty-eight male Wistar rats were randomly divided into 4 groups including sham con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Moreover, histopathological changes further confirmed the BDL-induced liver injury. These findings are in line with the study by Gheitasi et al 33 . An increase in these enzymes reflects the deterioration of structural integrity and permeability of hepatocytes membrane by the toxic bile salts' detergent effect, allowing these enzymes to escape into the blood 34 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, histopathological changes further confirmed the BDL-induced liver injury. These findings are in line with the study by Gheitasi et al 33 . An increase in these enzymes reflects the deterioration of structural integrity and permeability of hepatocytes membrane by the toxic bile salts' detergent effect, allowing these enzymes to escape into the blood 34 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, Omezzine et al [ 85 ] documented a relation between inhibited apoptotic cell death pathway by testosterone in the ventral prostate and reduced both caspase-3 and -6 mRNA production. A recent study also observed the exhibited induction of BPH together with reduced caspase activity [ 63 ]. The resistance to induce cellular apoptosis results in increased severity of BPH and might progress to prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between oxidative stress and BPH was previously reported with a significant reduction in serum and prostate antioxidant levels in BPH rats [ 5 , 33 , 58 ]. Previous studies reported the antioxidant activity of O. majorana against renal and hepatic injuries [ 36 , 37 , 63 ] and attributed this property to the effect of its secondary metabolites, particularly flavonoids, in preventing oxidative cell damage through their water-soluble effects [ 64 ], in addition to its inhibiting effect on the DPPH (2, 2-diphenyl-1-picrylhydrazyl) [ 38 ]. These reports are consistent with our data considering reduced prostatic MDA content and elevated prostatic SOD content with O. majorana .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported that the antioxidants mitigate BDL-induced liver injury ( 29 54 ). There is much evidence that herbal medicine including Origanum majorana ( 55 ), and Nasturtium officinale ( 29 ) has hepatoprotective effects through antioxidative effects against BDL-induced cholestasis. The antioxidant activity of JE essential oils and extracts was determined ( 56 ).…”
Section: Discussionmentioning
confidence: 99%